2017
DOI: 10.1017/s1092852917000220
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the long-term safety and tolerability of cariprazine in patients with schizophrenia: results from a 1-year open-label study

Abstract: Objective. Cariprazine, a dopamine D 3 /D 2 partial agonist atypical antipsychotic with preferential binding to D 3 receptors, is approved for the treatment of schizophrenia and manic or mixed episodes associated with bipolar I disorder. The efficacy and safety of cariprazine was established in three randomized, double-blind, placebocontrolled, 6-week trials in patients with acute exacerbation of schizophrenia. This 53-week study evaluated the longterm safety and tolerability of cariprazine in patients with sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
2
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 35 publications
4
47
2
5
Order By: Relevance
“…Механизм действия В сентябре 2015 г. Управление по контролю качества пищевых продуктов и лекарственных средств США одобрило первый атипичный нейролептик третьей генерации -карипразин. Основная отличительная особенность данного класса нейролептиков -более высокая аффинность к D3-рецепторам, превышающая аффинность даже самого дофамина [3][4][5][6][7][8]. Следует напомнить, что центральные D3-рецепторы широ-ко представлены в коре больших полушарий и стволе головного мозга, но в основном сконцентрированы в лимбических областях и прилежащем ядре.…”
Section: частичные агонисты D3-рецепторовunclassified
See 2 more Smart Citations
“…Механизм действия В сентябре 2015 г. Управление по контролю качества пищевых продуктов и лекарственных средств США одобрило первый атипичный нейролептик третьей генерации -карипразин. Основная отличительная особенность данного класса нейролептиков -более высокая аффинность к D3-рецепторам, превышающая аффинность даже самого дофамина [3][4][5][6][7][8]. Следует напомнить, что центральные D3-рецепторы широ-ко представлены в коре больших полушарий и стволе головного мозга, но в основном сконцентрированы в лимбических областях и прилежащем ядре.…”
Section: частичные агонисты D3-рецепторовunclassified
“…Возможно, это указывает на их регулирующую функцию дофаминергических сигналов в мезолимбической системе -ключевом нейроанатомическом субстрате развития психотической симптоматики при шизофрении, согласно дофаминовой гипотезе [4,7]. Кроме того, карипразин является частичным агонистом D2-рецепторов, как и представленные в настоящее время на рынке арипипразол и брекспипразол (последний в РФ не зарегистрирован), а также частичным агонистом рецептора серотонина 5-HT1A и антагонистом рецепторов 5-HT2B и 5-HT2A [8,9].…”
Section: частичные агонисты D3-рецепторовunclassified
See 1 more Smart Citation
“…6 Cariprazine is approved for the treatment of adult patients with schizophrenia (United States and Europe; recommended dose range: 1.5-6 mg/day) and manic or mixed episodes associated with bipolar I disorder (United States; recommended dose range: 3-6 mg/day). Clinical trials included in the development programs for schizophrenia and bipolar mania have demonstrated the efficacy, safety, or tolerability of cariprazine in adult patients [7][8][9][10][11][12][13][14][15][16] ; in these studies, blood samples were collected for the measurement of plasma concentrations of cariprazine and its major metabolites.…”
mentioning
confidence: 99%
“…There are generic measures specifically designed for non-clinical populations exploring global concerns that are not necessarily unique to a schizophrenic population. On the other hand, specific measures such as the schizophrenic quality of life scale revision 4 (SQLS-R4, 6), has been identified as a particularly useful measure for understanding how symptoms of schizophrenia effect the patient's QoL (3,8,9). The SQLS-R4 is a self-report measure comprising 33 items from which two domains of QoL, psychosocial feelings (22 items, e.g.…”
mentioning
confidence: 99%